Neutrality vs. social justice: a democratic perspective - Casper Hvenegaard Rasmussen; Nanna Kann-Rasmussen (Information Research: An International Electronic Journal)
Introduction. In recent years, there has been heated debate about the relationship between neutrality and social justice in library and information science. This intense dialogue is explicitly linked to democracy, yet, with few exceptions, the rich literature on democracy is not incorporated into the ongoing debate. The aim of this paper is to use theories on democracy as a lens to understand the ideological battle between neutrality and social justice.